2015
DOI: 10.1016/j.joep.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Group payoffs as public signals

Abstract: We study experimentally the effect on individual behavior of comparative, but payoff-irrelevant, information in a near-minimal group setting. Specifically, in each round, group members see the groups' cumulative payoffs, which consist of an aggregation of the earnings of each member of the group in the round. Our novel experimental design incorporates two games (the Trust game and the Dictator game) whose payoffs are carefully chosen to ensure cross-game comparability. In the baseline, no comparative informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Strong in-group biases have been found by Chen and Chen (2011), Charness et al (2007) or Chakravarty and Fonseca (2014) in designs that were not truly minimal. Ioannou et al (2016) find in-group biases only in settings where group identity is reinforced by displaying group payoffs. There is also strong evidence of the role of priming in reinforcing identity-based behaviour and preferences (Benjamin et al, 2010;Van Bavel et al, 2008).…”
mentioning
confidence: 82%
“…Strong in-group biases have been found by Chen and Chen (2011), Charness et al (2007) or Chakravarty and Fonseca (2014) in designs that were not truly minimal. Ioannou et al (2016) find in-group biases only in settings where group identity is reinforced by displaying group payoffs. There is also strong evidence of the role of priming in reinforcing identity-based behaviour and preferences (Benjamin et al, 2010;Van Bavel et al, 2008).…”
mentioning
confidence: 82%
“…However, because trustees have a selfish temptation to keep the entire amount for themselves, such cooperation by investors is potentially costly and involves the risk of exploitation by their trustee. While some studies found that participants give more money to ingroup compared to outgroup trustees (e.g., Fershtman & Gneezy, 2001; Hargreaves Heap, Verschoor, & Zizzo, 2009; Ioannou, Qi, & Rustichini, 2012), other studies found no evidence of intergroup discrimination in the trust game (Güth, Levati, & Ploner, 2008; Johansson-Stenman, Mahumud, & Martinsson, 2005).…”
Section: Intergroup Discrimination In Cooperationmentioning
confidence: 97%
“…Falk & Zehnder (2013) frame the results of their field experiment in terms of, "in-group effects" rather than out-group effects. Similarly, Ioannou et al (2015) posit that one of their experimental treatments is, "sufficient to invoke an in-group bias" in trust and dictator games, when only comparing behaviour from in-group and out-group interactions. As Goette et al (2006) highlight, in-group favouritism and out-group negativity produce the same predicted outcome, and are indistinguishable when a baseline or group-neutral comparison is excluded.…”
Section: Table 3: Summary Statisticsmentioning
confidence: 99%
“…One explanation for why we do not observe in-group favouritism could be that the English treatment is not a strong enough experimental manipulation, or it was unsuccessful in inducing an in-group sense of identity. To shed light on this, we examine self-reported levels of group attachment, or Closeness, as is standard in the literature (Chen & Li, 2009;Ioannou et al, 2015;Yamagishi & Kiyonari, 2000).…”
Section: Table 3: Summary Statisticsmentioning
confidence: 99%